Implementasi Sistem Pakar Kerusakan Motor Vespa Dengan Metode Teorema Bayes - Saiful Nurarif; Iskandar Zulkarnain; Sobirin (Universitas Harapan Medan, 2021)
Vespa began to be favored by young people, especially the antique vespa, precisely the 1967 Sprint S vespa, this is because this motorcycle has a uniqueness. Unlike other motorcycles, detecting damage to the 1967 Vespa Sprint S is much more difficult than normal motorcycles. In order to make it easier in the process of detecting a damage to the Vespa, a sister system was made, namely the Expert System. Expert systems are usually used to detect damage or detect damage whose symptoms have a probability value or weight obtained from an expert. From this research obtained a system that can detect damage to the Vespa Sprint S 1967 so that it helps every owner of this vehicle in detecting the damage and making repairs to overcome the damage